Evaluation of required connection load in GRS-IBS structures under service loads. Issue 6 (19th December 2020) - Gebremariam, F.; Tanyu, B. F.; Christopher, B.; Leshchinsky, D.; Zornberg, J. G.; Han, J.
Abstract : This study presents an evaluation of the connection load ( To ) and stress-strain conditions right behind the facing of a Geosynthetic Reinforced Soil – Integrated Bridge Structure (GRS-IBS) based on field instrumentation data obtained from an abutment constructed in Virginia. The observations from this site are compared against other projects in Delaware and Louisiana. The lateral stress distribution obtained from the field was observed to be lower than the active lateral earth pressure distribution but higher than predicted using the bin pressure method. The results from all sites showed that the reinforcement strains measured in the field were below the maximum geosynthetic strains allowed in the design of GRS-IBS. The distributions of both lateral stresses and reinforcement strains with depth were found to be approximately uniform. The To values for the Virginia structure were obtained based both on reinforcement strain and lateral stress data, which agreed well with each other. All sites indicated the existence of lateral stresses behind the facing, which contributed to the development of To . The normalized To values for all GRS-IBS projects evaluated in this study showed that the theoretical tributary area approach outlined in MSE design can be conservatively adopted to predict To in the design of GRS-IBS.